2018
DOI: 10.1002/berj.3470
|View full text |Cite
|
Sign up to set email alerts
|

Track recommendation bias: Gender, migration background and SES bias over a 20‐year period in the Dutch context

Abstract: Bias in track recommendations is an important mechanism, which causes education inequity in a tracked educational system (streaming). If teacher biases in track recommendations change over time, inequity in society and in the education system may also change. We investigated changes in track recommendation bias over time for gender, immigration status and socioeconomic status (SES), based on a longitudinal empirical study of nine cohorts of Dutch students in their final year (grade 6) of primary education in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
52
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 30 publications
6
52
0
1
Order By: Relevance
“…After that, di erent ethnic groups seemed to receive comparable educational recommendations given equal school performance (Driessen et al, 2008). In agreement with the conclusion by Timmermans et al (2018), according to the inspectorate of Education in the Netherlands (2019), ethnicity nowadays indeed plays a lesser role in track allocation. Other studies, however, still report a disadvantage for non-native pupils (see Baysu, Alanya & Van De Valk, 2018;Scheerens & Van Der Werf, 2018).…”
Section: Literature Reviewsupporting
confidence: 77%
See 3 more Smart Citations
“…After that, di erent ethnic groups seemed to receive comparable educational recommendations given equal school performance (Driessen et al, 2008). In agreement with the conclusion by Timmermans et al (2018), according to the inspectorate of Education in the Netherlands (2019), ethnicity nowadays indeed plays a lesser role in track allocation. Other studies, however, still report a disadvantage for non-native pupils (see Baysu, Alanya & Van De Valk, 2018;Scheerens & Van Der Werf, 2018).…”
Section: Literature Reviewsupporting
confidence: 77%
“…Focusing on research from the Netherlands, Luxembourg and Flanders 27 (the northern part of Belgium), multiple studies have indicated that a pupil's gender, socio-economic status (SES) and ethnicity might influence the judgment of the teacher (see, for instance, Timmermans, De Boer, Amsing & Van Der Werf, 2018). Especially SES is almost consistently found to influence track recommendations after performance on the EPST-test is taken into account (Geven et al, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…6 Such a pattern might reflect institutionalised discrimination -inequities embedded in policies or procedures of organisations -as the school transition system allows room for bias in track recommendations. 7 Such bias is likely to be strengthened if a climate of nativism arises as propagated by PRR parties, whereby immigrants are framed as a collective threat to exacerbate collective insecurity. 8 In addition, although PRR parties generally seem to favour quality education, they also show tendencies towards strengthening national identity through education and emphasising free choice for parents for access to high-quality education.…”
Section: Multifaceted Causal Pathways That Link the Populist Radical mentioning
confidence: 99%